If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = (3w + -8) + -35 Reorder the terms: 0 = (-8 + 3w) + -35 Remove parenthesis around (-8 + 3w) 0 = -8 + 3w + -35 Reorder the terms: 0 = -8 + -35 + 3w Combine like terms: -8 + -35 = -43 0 = -43 + 3w Solving 0 = -43 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. 0 + -3w = -43 + 3w + -3w Remove the zero: -3w = -43 + 3w + -3w Combine like terms: 3w + -3w = 0 -3w = -43 + 0 -3w = -43 Divide each side by '-3'. w = 14.33333333 Simplifying w = 14.33333333
| 2.7z=1.2z-9 | | 3x^2+3x=40 | | 3x^2+3x=25 | | x^2+5=20 | | 7ln(6x)=63 | | -3f/5=-4/15 | | 8y-4=6y+4 | | 6x+3=-33 | | 9(-x+4)=15 | | 4y-2=4y+2 | | 0.3w-4=.8-.2w | | 5+2qrstx=9 | | .75-9p=-0.6 | | 5/14=-2a/7 | | 50b+2.25=1.75 | | -3+2w+5.67-2.44w= | | 5/14=-2e/7 | | 5(3b^2-2b)+10b^2-1= | | -3k^2-7k=0 | | 3x=7x+12 | | 18(x-3)=19 | | -x^2+8x-2=0 | | 8+5x=33 | | ex=7x+12 | | 4-2x=12+6x | | 2w-3(w)-65=0 | | 5(3b*2-2b)+10b*2-1= | | 4(-2-3X)=[-6X-5(8-6X)] | | (4x^3)-(36x^2)+(96x)-(64)=0 | | 4.571428571a^2=1-7.428571429a | | x^2+38x+13= | | 5x+3y=63 |